65.2k views
3 votes
Solve y = −23(x + 9) + 4 for x when y = 0.

2 Answers

1 vote

Answer:

-203

Explanation:

remove the 0 ( when adding or substracting 0, the quantity does not change

y=-23 (9+4)

Multiply the numbers -23x9

y= =207+4

Calculate the sum

y= -207+4

Which = -203

User Farhang Amaji
by
5.2k points
4 votes

Answer:

x = -203/23

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

  • Multiplication Property of Equality
  • Division Property of Equality
  • Addition Property of Equality
  • Subtraction Property of Equality

Explanation:

Step 1: Define

Identify

y = -23(x + 9) + 4

y = 0

Step 2: Solve for x

  1. Substitute in y: 0 = -23(x + 9) + 4
  2. [Subtraction Property of Equality] Subtract 4 on both sides: -4 = -23(x + 9)
  3. [Division Property of Equality] Divide -23 on both sides: 4/23 = x + 9
  4. [Subtraction Property of Equality] Subtract 9 on both sides: -203/23 = x
  5. Rewrite: x = -203/23
User Myo
by
5.8k points